Understanding the Relative Impact of Dual Identification on Brand Loyalty on Social Media: The Regulatory Fit Perspective in Different Cultures - Chen, Shang; Min, Qingfei; Xu, Xuefei (Frontiers in Psychology, 2022)
This study explorers whether the relative impacts of brand identification and identification with other users of brand pages on brand loyalty vary according to consumers’ regulatory focus. By integrating social identification theory with regulatory focus theory, this study adopts a dual identification framework to compare the differential impacts of promotion regulatory fit and prevention regulatory fit on brand loyalty. Besides, the moderating effects of product type on the relationship between promotion/prevention regulatory fit and brand loyalty are further investigated. Finally, this study uses different combinations of IT affordances in order to examine their influences on each identification target. The current study adopts a qualitative methodology and involved conducting semi-structured interviews with 27 brand page users in regard to IT affordances and their subdimensions. The research model was empirically tested using a cross-country comparison of data collected from surveys conducted in China and the United States. The results support our hypotheses and confirm the differential effects of promotion and prevention regulatory fit on brand loyalty. Theoretically, our study enhances our understanding of the relative effect of dual identification on brand loyalty on social media. Practically, our study delivers insights for companies into how social media brand pages can be used as a strategic tool to achieve brand values.